Recognizing & engaging employees for dummies - Nelson, Bob, 1956- (--For dummies., 2015)
Improve engagement, productivity, and motivation with effective employee recognition Recognizing and Engaging Employees for Dummies gives you the tools and information you need to improve morale, productivity, and personal achievement with a successful employee recognition program. Written by a world-leading authority in employee recognition, this book walks you step-by-step through the design and implementation process and describes the incentives that work, the behaviors to reward, and the mechanisms that must be in place for the program to be effective in the long term. You'll learn how t.